PELAKSANAAN TANGGUNG JAWAB ORANG TUA KATOLIK MENDIDIK IMAN ANAK DI MASA PANDEMI - Wijayanti, Tunas; Wijaya, Albert I Ketut Deni (Bahasa Indonesia, 2024)
This research explored the implementation of parental responsibilities in children's faith education during the coronavirus pandemic. Faith education for children is the first and foremost responsibility of parents. However, during the Corona Virus disease pandemic, there was a challenge: restrictions on church activities. It was the responsibility of parents to educate their children's faith. This research method used descriptive qualitative data analysis, while the data collection used structured interviews. Narrative writing is the way to present the research findings. The results showed the implementation of faith education for children during the coronavirus pandemic by teaching daily prayers, attending the online Eucharist, and faith education. In this implementation, there were some challenges: parents must be patient, and children's addiction to mobile phones. Parents continue to strive to teach daily prayer, follow the Eucharist online, and give faith education. From implementing faith education for children during the coronavirus pandemic, parents are responsible for accompanying and educating their children's faith according to their conditions.